АНАЛИЗ ГЕМОСТАЗИОЛОГИЧЕСКИХ НАРУШЕНИЙ У БОЛЬНЫХ С ИММУННОЙ ТРОМБОЦИТОПЕНИЕЙ - Маткаримова Д.С.; Жахонов А.Х. (Journal of new century innovations, 2024)
Material and methods. The study included 68 patients with ITP, who, according to the stage of the disease. All the subjects were under observation or inpatient treatment at the Khorezm Regional Multidisciplinary Medical Center (HRMMC). The control group consisted of conditionally healthy persons of comparable age without immunocomplex pathologies and disturbances in the hemostasis system (n= 30). All subjects were subjected to a study of indicators of the hemostasis system, on a coagulometer HumaClot Junior (HC-4127, Germany) using reagents "HUMAN, Germany". Statistical processing of the obtained data was carried out by the method of variation statistics using the Microsoft Office Excel-2014 program.